PENAFSIRAN HAKIM TENTANG KEBERADAAN STRUKTURAL LEMBAGA KEPOLISIAN SEBAGAI PENYELENGGARA NEGARA DAN PENEGAK HUKUM (KAJIAN TERHADAP PUTUSAN PENGADILAN NEGERI JAKARTA SELATAN NOMOR 04/PID.PRAP/2015) - R. Yosia Simamora (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The Corruption Eradication Commission (KPK) announced BudiGunawan as a suspect of corruption when he was Deputy Head of CareerDevelopment of Human Resources. South Jakarta District Court panel ofjudges Sarpin Rizaldi favor Budi Gunawan and express stipulation assuspect unauthorized and not legally binding. In its decision, the judgestated that the determination Sarpin Rizaldi Budi Gunawan suspects by theKPK is not legally valid. Judges considered that the Commission had noauthority to investigate cases that ensnare Budi Gunawan, because whenthe suspect is not included as an organizer of the state and law enforcer.With a variety of the above problems, the authors are keen to lift the titlethesis on